2011
DOI: 10.1021/ef101698g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Composition on sII Hydrate Growth Kinetics

Abstract: Kinetics of hydrate formation is of paramount importance for hydrate prevention in pipelines and gas storage in a hydrate state. The effect of gas composition on the kinetics of structure II (sII) hydrate growth has been examined by using two different synthetic natural gases, one with two components (SNG2) and the other with seven components (SNG7). The hydrate equilibrium properties of SNG2 and SNG7 were comparable and the initial degree of subcooling was thus approximately the same during all growth experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…The literature regarding this differs significantly. Abay et al 10 report that the growth kinetics of sII gas hydrates are dependent on the hydrate formed and not on the additives. This is in accordance with other authors who found the growth rate not to be or only slightly influenced by the addition of salt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature regarding this differs significantly. Abay et al 10 report that the growth kinetics of sII gas hydrates are dependent on the hydrate formed and not on the additives. This is in accordance with other authors who found the growth rate not to be or only slightly influenced by the addition of salt.…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with the work of Moeini 9 et al who also found the overall gas uptake for CO 2 gas hydrates highly influenced by dissolved NaCl. On the other hand, Abay et al, 10 who studied the formation of different synthetic natural gases, state that the kinetics of hydrate formation are not influenced by additives but only depend on the gas species. This is consistent with the work of Farhang et al, 11 who found the growth rate of CO 2 gas hydrates with the addition of different sodium halides only slightly influenced.…”
Section: Introductionmentioning
confidence: 99%
“…Their comparison of the results for methane and natural gas seems to also suggest that, at constant subcooling, the gas composition has no effect on the hydrate growth rate. However, this needs to be further investigated, because work by Abay et al [99] with two different synthetic natural gas compositions showed that the composition had an effect on the hydrate growth rate, with the seven-component synthetic natural gas having a growth rate double that of the two-component synthetic natural gas. Figure 12.…”
Section: Effect Of Experimental Temperature and Subcoolingmentioning
confidence: 99%
“…The growth rate of CO 2 hydrate first increased toward a maximum value after hydrate onset and then decreased toward zero at the end of experiment. This consistency in growth pattern is compatible with the fact mentioned by Abay et al (2011) that the overall pattern of hydrate growth is a fingerprint of the effect of gas hydrate former rather than additives. In the system with pure water, the amount of hydrate formed is very small.…”
Section: Induction Timesupporting
confidence: 88%